การเสริมสร้างความรู้ความเข้าใจด้านการศึกษาและอาชีพ เพื่อรองรับการเข้าสู่ประชาคมอาเซียนสำหรับนักศึกษา วิทยาลัยเทคโนโลยีเทคนิควิชาชีพสกลนคร - หทัยชนก สมบูรณ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This purposes of this study were 1) to study activities to Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. 2) to study the results of investigate Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. The populations were 30 students of vocational certificate level 1 Diploma of business computing studying in the in Sakon Nakhon Technical Vocations Technology College of Sakon Nakhon province the second semester, academic year 2013. The research instruments consisted of 1) lesson plans for Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. 2) Test of Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. 3) Questionnaire on student’s satisfaction for learning Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. The data were analyzed by using frequency, percentage, means and standard. The findings of the study were as follows: 1. The study activities to Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community the study was 5 lesson plans totally 20 teaching hours. 2. The result test measures to Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. Mean score of pretest amount 19.63 and mean score of posttest amount 24.96. The posttest score was statistical higher than the pretest score. 3. The result assessment of satisfaction for learning Enhancing Knowledge and Understanding of Education and Career in Joining ASEAN community. The content has average of 3.91 to be satisfied at a high level. The activities have average of 3.85 to be satisfied at a high level. And the media, materials, equipment have average of 3.98 to be satisfied at a high level.